The Utility of a Portable Sleep Monitor to Diagnose Sleep-Disordered Breathing in a Pediatric Population - Colin Massicotte; Suhail Al-Saleh; Manisha Witmans; Indra Narang (Canadian Respiratory Journal)
BACKGROUND: Central and/or obstructive sleep-disordered breathing (SDB) in children represents a spectrum of abnormal breathing during sleep. SDB is diagnosed using the gold standard, overnight polysomnography (PSG). The limited availability and access to PSG prevents its widespread use, resulting in significant delays in diagnosis and treatment of SDB. As such, portable sleep monitors are urgently needed.